2015
DOI: 10.1021/acs.est.5b01464
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sediment on Agrichemical Fate and Bioavailability to Adult Female Fathead Minnows: A Field Study

Abstract: Precipitation induced runoff is an important pathway for agrichemicals to enter surface water systems and expose aquatic organisms to endocrine-disrupting compounds such as pesticides and steroid hormones. The objectives of this study were to investigate the distribution of agrichemicals between dissolved and sediment-bound phases during spring pulses of agrichemicals and to evaluate the role of suspended sediment in agrichemical bioavailability to aquatic organisms. To accomplish these objectives, suspended s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 62 publications
3
26
0
Order By: Relevance
“…Exposure of all fathead minnow larvae was conducted at the Elkhorn River Research Station (ERRS) where previous field studies have identified biological impacts and changes in endocrine responsive gene expression following in situ exposure to agricultural runoff (Knight et al 2013;Ali and Kolok 2015;Zhang et al 2015;Ali et al 2016). The ERRS is an open-air facility located approximately 10 km upstream from the confluence of the Elkhorn and Platte Rivers, Nebraska, USA.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 99%
See 4 more Smart Citations
“…Exposure of all fathead minnow larvae was conducted at the Elkhorn River Research Station (ERRS) where previous field studies have identified biological impacts and changes in endocrine responsive gene expression following in situ exposure to agricultural runoff (Knight et al 2013;Ali and Kolok 2015;Zhang et al 2015;Ali et al 2016). The ERRS is an open-air facility located approximately 10 km upstream from the confluence of the Elkhorn and Platte Rivers, Nebraska, USA.…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 99%
“…The ERRS is an open-air facility located approximately 10 km upstream from the confluence of the Elkhorn and Platte Rivers, Nebraska, USA. The station is equipped to pump water continuously from the Elkhorn River into stainless steel mesocosms capable of supporting aquatic organisms Zhang et al 2015;Ali et al 2016).…”
Section: Exposure At the Elkhorn River Research Stationmentioning
confidence: 99%
See 3 more Smart Citations